Predicting burnout in early-career school counselors: The role of hope and school counselor job activities - Scott, Melanie (My University, 2026)
Early-career school counselors face role ambiguity when the duties assigned by administration do not align with the school counselor’s skills and expertise acquired in their preparatory program. This quantitative study examined the alignment between early-career school counselors’ expected and actual job activities and explored whether discrepancies between the two are associated with burnout. It further studied whether hope and its subfactors influenced burnout within the first five years of an early-career school counselor’s profession. Convenience sampling was used to recruit early-career school counselors serving in the first five years of their profession as a full-time school counselor. An email invitation to participate in the online survey was sent to school counselor program coordinators and school counseling associations in the North Central Association for Counselor Education and Supervision (NCACES) region as well as posted on the American School Counselor Association (ASCA) Member Community Open Forum. Participants voluntarily completed the following instruments: Trait Hope Scale (n=85), Counselor Burnout Inventory (n = 80), SCARS Modified (ASCA Expected) Survey (n = 79), SCARS Modified (ASCA Actual) Survey (n = 75), and the Early-Career School Counselor Demographic Survey (n = 75). The findings of this study revealed misalignment on many activities the school counselors were asked to perform. The results also showed a significant negative correlation between the alignment and burnout, indicating the higher the misalignment, the higher the level of burnout. Furthermore, the results indicated a significant negative relationship between hope and burnout, indicating hope mitigates burnout. The implications of the findings, limitations, as well as recommendations for future practice and research are further discussed.
Keywords: Early-career school counselors; Burnout; Hope; Role of a school counselor; Professional identity; School counselor activities